(3GdJHjGf aj BOGH MedI GdbQBfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s ((3HOQ GdOjf Hf eMeO Hf YeQ Hf YKeGf GdHQfGhi s)
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdefGf , Pi GdWhd hGdaVd hGdEMSGf , GdPi gOGfG ddEjeGf s
(3BNQgG (B:s
(3hbO HSWJ HjGfg ai JgPjH GdCSeGA hGddZGJ agPg CMQa hLjRI ai VHW eTcd eG hbY ai gPG GdcJGH gPG BNQ eG JjSQef gPG GdcJGH hgh fHP eNJUQI HGdfSHI Edi BOGH GdbQGA s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs